1975
DOI: 10.1128/jb.124.1.190-200.1975
|View full text |Cite
|
Sign up to set email alerts
|

Nucleic acid synthesis and ribonucleic acid polymerase specificity in germinating and outgrowing spores of Bacillus subtilis

Abstract: Nucleic acid synthesis was studied during germination and outgrowth of normal spores of Bacillus subtilis, as well as of spores carrying the genome of phage oe. In a system in which development was restricted to the spore-darkening phase, synthesis of ribonucleic acid (RNA), but not deoxyribonucleic acid (DNA), was detected. The extent of RNA synthesis and turnover during this phase was similar for the two types of spores. In a partially darkened population of spores of either type, there was little RNA degrad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

1976
1976
1995
1995

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…However, the difficulty with which E-A is isolated from sporulating cells (25,182) and the loss of bacteriophage gene expression (25,185) following the onset of sporulation suggest that once the early sporulation genes are expressed, A may become largely inactive. If this is so, the possible synthesis of A late in sporulation (242) could represent a device to provide the spore with A that is inactivated and stored for use during germination and outgrowth (33).…”
Section: Isolation and Characterizationmentioning
confidence: 99%
“…However, the difficulty with which E-A is isolated from sporulating cells (25,182) and the loss of bacteriophage gene expression (25,185) following the onset of sporulation suggest that once the early sporulation genes are expressed, A may become largely inactive. If this is so, the possible synthesis of A late in sporulation (242) could represent a device to provide the spore with A that is inactivated and stored for use during germination and outgrowth (33).…”
Section: Isolation and Characterizationmentioning
confidence: 99%
“…Phage infection of Bacillus has been used to explore the control mechanisms associated with the switchover from vegetative growth to sporulation (6, 9,17) and from dormancy to active growth (3,5). Such studies have indicated that, relative to the capacity for phage production during vegetative growth, phage production at other stages in the cell's life cycle is greatly diminished.…”
mentioning
confidence: 99%
“…Also, the finding that the RNA synthesis during the early stages of germination is not temperature sensitive in the mutant (Fig. 7) could be explained if, under these conditions, the synthesis of RNA does not depend on sigma factor (5). The effect of the rna-53 mutation on phage SPP1 transcription in vivo (Fig.…”
Section: Discussionmentioning
confidence: 93%
“…The block of transcription at the restrictive temperature is suppressed by a protein synthesis inhibitor such as chloramphenicol (Fig. [3][4][5], indicating that a metabolically unstable inhibitor might be responsible for the observed effect. The possibility that such an inhibitor is a protease seems very unlikely in view of the experiment shown in Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation